Electro-Mechanical Engineer Degree Level Apprenticeships: An initial reflection on improving distance-learner engagement and motivation (UK and Ireland Engineering Education Research Network Conference Proceedings 2023, 2024)
This concept paper discusses the proposed implementation of learning supports via motivational scaffolding as method for improving engagement and motivation of Electro-Mechanical Engineering degree-level apprentices at the University of Nottingham. The paper focuses on a block-release programme where a large proportion of learning occurs online asynchronously. These apprentices have generally entered degree-level study from background vastly different from typical undergraduate students. Combined with the management of their normal job with their university study, there is a step-change in mind set required to be successful on the programme. Anecdotal feedback has previously suggested that around half of the apprentices on the programme found it challenging to settle into a successful work pattern within the first 6 weeks of the programme. The proposed intervention aims to provide learners with the environment to learn and excel rather than spending time finding the study materials, or working out what is required of them. The intervention was developed in conjunction with a focus group of apprentices and a scoping survey released to all cohorts on the programme. The success of the intervention will be evaluated over the next academic year through further feedback surveys, focus group discussions and comparison of grades and engagement of online content.